2-Hydroxybenzophenone Derivatives: ESIPT Fluorophores Based on Switchable Intramolecular Hydrogen Bonds and Excitation Energy–Dependent Emission - Wang, Hailan; Xiao, Yuxin; Xie, Zongliang; Sun, Haodong; Zhang, Xiayu; Wang, Juan; Huang, Rongjuan (Frontiers in Chemistry, 2021)
We have developed a series of excited-state intramolecular proton transfer (ESIPT) emitters, BPOH-TPA, BPOH-SF and BPOH-PhCz, by substituting different donor moieties on the acceptor, 2-hydroxybenzophenone (BPOH). All molecules exhibit dual-emission in solutions. While broad emission spectra were observed in solid state with a low energy excitation power (1 mW/cm2). By increasing the excitation energy, dual-emission with a low-energy band ranging from 550 to 582 nm and a high-energy band ranging from 625 to 638 nm were obtained in all three molecules. To further illustrate the excitation-dependent emission, photophysical studies and single crystal analyses were performed. BPOH-TPA with a stronger donor strength exhibited a more obvious color change gradually from yellow with the Commission Internationale de l'éclairage (CIE) coordinates of (0.40, 0.50) to orange with the CIE coordinates of (0.42, 0.43) with the increasing excitation power from 1 mW/cm2 to 15 mW/cm2. This study provides a novel example of ESIPT materials with tunable emission colors.